Pencegahan Pencemaran Nama Baik Menurut Perundang - Undangan Dan Hukum Islam Di Kota Medan - Sutan Fachrezy Damanik; Anwar Sadat (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This thesis aims to find out the prevention of defamation laws according to the law and Islamic law in the city of Medan. Data collection in this study was carried out by means of literature studies and interviews. In this study, legal data were qualitatively analyzed rules and techniques to satisfy the researcher's curiosity in a juridical symptom or a way to find the truth and acquire knowledge. The results showed that the Application of defamation rules in Article 310-318 of the Criminal Code and ITE Law No. 19 of 2016 amends Law no. 11 of 2008 in handling defamation, in writing, verbally, and hate speech on social media against perpetrators tend to be repressive (use of power outside the corridors of the law). The contribution of law enforcement of criminal defamation by the police to the criminal law, cannot be said to be effective Islamic law has not specifically addressed the types of defamation and penalties so it has not been able to effectively regulate the prevention of defamation in Islamic law. The development of this law regarding defamation does not pay attention to the social dynamics that exist in society. It can be seen from the problem of defamation that many occur through social medicine whose events are still difficult to prove.